2013
DOI: 10.1257/aer.103.1.305
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Country Differences in Productivity: The Role of Allocation and Selection

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
587
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 877 publications
(671 citation statements)
references
References 30 publications
39
587
0
8
Order By: Relevance
“…This is how the mechanism of allocative efficiency works in developed market economies. A similar trend was found in the developing economies of Eastern Europe where there was very low or even negative allocative efficiency at the beginning of the transition period and only later did it improve significantly [Bartelsman et al, 2013]. In contrast, there are still no clear indications of improving allocative efficiency in Russia.…”
Section: Determinants and Patterns Of Sme Growth: The Russian Contextsupporting
confidence: 71%
See 1 more Smart Citation
“…This is how the mechanism of allocative efficiency works in developed market economies. A similar trend was found in the developing economies of Eastern Europe where there was very low or even negative allocative efficiency at the beginning of the transition period and only later did it improve significantly [Bartelsman et al, 2013]. In contrast, there are still no clear indications of improving allocative efficiency in Russia.…”
Section: Determinants and Patterns Of Sme Growth: The Russian Contextsupporting
confidence: 71%
“…This is the main motivation for growth among the entrants. Empirical evidence from developed countries suggest that firms follow an "up-or-out" dynamic where small firms are more likely to go bankrupt than larger firms, but in the case of success, the chances for growth rise [Bartelsman et al, 2013;Navaretti et al, 2014;Geurts, van Biesebroeck, 2016, etc.]. In general, the average size of a firm will double after 5-10 years on the market, but only fifty percent of entrants will survive [Geurts, van Biesebroeck, 2016].…”
Section: Determinants and Patterns Of Sme Growth: The Russian Contextmentioning
confidence: 99%
“…If firms are weighted by size (note that employment and output are proportional to the idiosyncratic draw of z i ), the weighted standard deviation of ln(TFP) turns out to be α/(ϕ − 1) ≈ 0.19. Both measures are smaller than the empirical measures of standard deviations of ln(TFP) for US firms within narrowly defined industries which average around 0.4 (see Hsieh and Klenow (2009) and Bartelsman et al (2013)). While model calibrations with more dispersion (i.e.…”
Section: Calibrationmentioning
confidence: 71%
“…OP argued that this was because the deregulation permitted inputs to be reallocated more readily from less to more productive US …rms. In a subsequent study, Bartelsman et al (2013) found that the OP covariance term for labor productivity averages about 50 log points within US manufacturing industries: this implies that the industry index of labor productivity in the average US manufacturing industry is 50 percent higher than it would be if employment shares were randomly allocated within industries. Bartelsman and his coauthors found however that the OP covariance term reaches only 20-30 log points in Western Europe and it was close to zero, if not negative, in Central and Eastern European countries at the beginning of their transition to a market economy.…”
Section: Literature Reviewmentioning
confidence: 97%
“…As I discussed in section 3, I decompose the total factor productivity index for …rms in Compustat as the sum of an unweighted component and a covariance component, following the methodology pioneered by Olley and Pakes (1996) and reprised by Bartelsman et al (2013):…”
Section: Great Recession Simulationmentioning
confidence: 99%